Effets de la périodisation de la prise de glucides sur les adaptations à l`entraînement - Marquet, L.-A.; Hausswirth, C.; Brisswalter, J. (Science & Sports, 2015)
Aims: The aim of this review is to provide new insights about the manipulation of carbohydrate (CHO) intake on training adaptations and endurance performance. Actualities: It has been recently shown that training with low CHO availability improves adaptations to endurance training. Some studies manipulated exogenous CHO availability while others manipulated endogenous CHO availability. As a result, training with a low CHO availability increases the mitochondrial biogenesis, endurance training adaptations and modifies the substrates oxidation during exercise. But in these studies no effects are observed on endurance performance. A new training strategy called "sleep low" training strategy has recently emerged. It integrates a double decreased CHO availability (exogenous and endogenous). Perspectives and prospects: Future studies are necessary to understand the impact of this new strategy on endurance training adaptations and performance. Is there a dose/response relationship between the levels of CHO decreased availability and performance? How this strategy has to be planned in an annual training program? It would also be interesting to evaluate the impact of this strategy on the perception of effort and on the immune function. Conclusion: Classically, CHO manipulation has been shown to be a regulator of endurance training adaptations. The strategy called "sleep low" seems to be an efficient strategy to optimize endurance training adaptations and to improve performance with a manipulation of the CHO availability and a periodization of the CHO intake during the training program.